Association Between Meeting Physical Activity Time-Intensity Guidelines With Ambulation, Quality of Life, and Inflammation in Claudication. Issue 6 (6th November 2022) - Gardner, Andrew W.; Montgomery, Polly S.; Wang, Ming; Shen, Biyi; Zhang, Shangming; Pomilla, William A.
Abstract : Patients with claudication who meet the 2018 physical activity time-intensity guidelines for US adults had better ambulation, quality of life, and vascular outcomes than those who failed to meet guidelines. Patients with claudication best achieved the guidelines by taking ≥7675 total steps/d, and ≥1660 steps/d at moderate cadence. Abstract : Purpose: The aim of this investigation was to determine if meeting the 2018 physical activity (PA) time-intensity guidelines was associated with better ambulatory function, health-related quality of life (HRQoL), vascular function, and inflammation than failing to meet the guidelines in patients with peripheral artery disease and claudication. Second, we determined the optimal number of total steps/d and steps taken at moderate cadence needed to meet the PA time-intensity guidelines. Methods: Five hundred seventy-two patients were assessed on daily ambulatory activity for 1 wk with a step activity monitor, and were grouped according to whether they achieved <150 min/wk of moderate-intensity PA (group 1 = do not meet guidelines; n = 397) or whether they were above this threshold (group 2 = meet guidelines; n = 175). Results: Treadmill peak walking time (mean ± SD) was higher ( P < .001) in group 2 (709 ± 359 sec) than in group 1 (427 ± 281 sec). The physical function HRQoL score was higher ( P < .001) in group 2 (61 ± 22%) than in group 1 (44 ± 21%). High-sensitivity C-reactive protein was lower ( P < .001) in group 2 (3.6 ± 4.5 mg/L) than in group 1 (5.9 ± 6.1 mg/L). Finally, ≥7675 total steps/d and ≥1660 steps/d at moderate cadence were optimal thresholds associated with meeting PA guidelines. Conclusions: Patients with claudication who meet the 2018 PA time-intensity guidelines for US adults had better ambulation, HRQoL, and vascular outcomes than those who failed to meet the PA guidelines. Patients with claudication best achieved the PA time-intensity guidelines by taking ≥7675 total steps/d, and ≥1660 steps/d at a moderate cadence.